2022
DOI: 10.3389/fgeed.2022.1050507
|View full text |Cite|
|
Sign up to set email alerts
|

CRISPR nuclease off-target activity and mitigation strategies

Abstract: The discovery of CRISPR has allowed site-specific genomic modification to become a reality and this technology is now being applied in a number of human clinical trials. While this technology has demonstrated impressive efficacy in the clinic to date, there remains the potential for unintended on- and off-target effects of CRISPR nuclease activity. A variety of in silico-based prediction tools and empirically derived experimental methods have been developed to identify the most common unintended effect—small i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 137 publications
(170 reference statements)
0
12
0
Order By: Relevance
“…In addition, on-target DSB may lead to large deletions, complex rearrangements, chromothripsis or aneuploidy and chromosomal truncations (83)(84)(85). Hence more controlled novel and safer CRISPR-Cas9 based tools would be desirable in the future for translation (63). Since we demonstrated that a minimal modification of the mRNA Let-7c BS, e.g.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, on-target DSB may lead to large deletions, complex rearrangements, chromothripsis or aneuploidy and chromosomal truncations (83)(84)(85). Hence more controlled novel and safer CRISPR-Cas9 based tools would be desirable in the future for translation (63). Since we demonstrated that a minimal modification of the mRNA Let-7c BS, e.g.…”
Section: Discussionmentioning
confidence: 88%
“…In summary, these data demonstrate that our CRISPR-Cas9 strategy targets utrophin 3'UTR with high efficiency and without major off-target effect. Additional studies to reduce offtargets (63) and indel quantification on edited muscles, normally exposed to lower gRNA/Cas9 concentration, will be performed before clinical translation.…”
Section: Scanning Utrophin 3'utr For Post-transcriptional Regulatory ...mentioning
confidence: 99%
“…Base editors can bind and modify off-target genomic loci with sequence homology to the target protospacer, similar to other genome editors 46 . As base editors rapidly advance towards clinical application, defining guide RNA (gRNA) dependent off-target activity of adenine base editors in a sensitive and unbiased way is important for ensuring the safety of these new therapeutic approaches 7 .…”
Section: Mainmentioning
confidence: 99%
“…The risk of off-target effects and other forms of genotoxicity is a concern when translating CRISPR-Cas to clinical protocols 31 . To confirm high specificity of our preferred CRISPR-AsCas12a gene editing strategy, we examined the off-target profile of the selected AsCas12a-crRNA #1 using CAST-Seq technology 32 which detects potential off-target sites by identification of translocations between the on-target and the putative off-target sites.…”
Section: Off-target Analysis With Cast-seq Confirms High Specificity ...mentioning
confidence: 99%